2017
DOI: 10.1002/ange.201706602
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects between Atomically Dispersed Fe−N−C and C−S−C for the Oxygen Reduction Reaction in Acidic Media

Abstract: Various advanced catalysts based on sulfur‐doped Fe/N/C materials have recently been designed for the oxygen reduction reaction (ORR); however, the enhanced activity is still controversial and usually attributed to differences in the surface area, improved conductivity, or uncertain synergistic effects. Herein, a sulfur‐doped Fe/N/C catalyst (denoted as Fe/SNC) was obtained by a template‐sacrificing method. The incorporated sulfur gives a thiophene‐like structure (C−S−C), reduces the electron localization arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 43 publications
3
47
0
2
Order By: Relevance
“…The two peaks at 164.0 and 165.2 eV can be described to S 2p 3/2 and S 2p 1/2 of thiophene-like C-S-C structure, respectively [32,33], while the third peak at 167.3 eV corresponds to sulfate species. The synergetic effects of N, S co-doping would significantly improve the ORR activity by reducing the electron localization around the Fe centers, and improve the interaction with oxygen, facilitating the four-electron pathway [34]. The high-resolution Fe 2p spectrum of Fe/NS/C-g-C 3 N 4 /TPTZ-1000 presents two major peaks at around 711 and 724 eV, corresponding to Fe 2p 1/2 and Fe 2p 3/2 , respectively (Figure 6f) [15,35].…”
Section: Resultsmentioning
confidence: 99%
“…The two peaks at 164.0 and 165.2 eV can be described to S 2p 3/2 and S 2p 1/2 of thiophene-like C-S-C structure, respectively [32,33], while the third peak at 167.3 eV corresponds to sulfate species. The synergetic effects of N, S co-doping would significantly improve the ORR activity by reducing the electron localization around the Fe centers, and improve the interaction with oxygen, facilitating the four-electron pathway [34]. The high-resolution Fe 2p spectrum of Fe/NS/C-g-C 3 N 4 /TPTZ-1000 presents two major peaks at around 711 and 724 eV, corresponding to Fe 2p 1/2 and Fe 2p 3/2 , respectively (Figure 6f) [15,35].…”
Section: Resultsmentioning
confidence: 99%
“…S6) before and after acid leaching showed that the -C-S-C-covalent bond can be stable in the acid solution. According to previous studies, -C-S-C-is beneficial for enhancing the catalytic activity of ORR [60,61]. The high-resolution Fe 2p spectrum of PmPDA-GR-Fe (Fig.…”
Section: Science China Materialsmentioning
confidence: 70%
“…The peaks at 168.2 eV and 169.4 eV can be ascribed to SOx species. The previous work has demonstrated that S‐doping can increase the ORR catalytic activity of Fe/N/C materials because of the electronegativity, polarizability and large atomic radius of S atom . Moreover, Figure F shows the high‐resolution spectrum of Fe2p, which can be separated into two pairs of peaks for Fe 3+ (725.2 and 713.5 eV) and Fe 2+ (722.4 and 710.8 eV), corresponding to the Fe 3 O 4 and doped‐Fe in the NCMs.…”
Section: Resultsmentioning
confidence: 88%